Distribution of hand function by age in individuals with Rett syndrome - Jeffrey L. Neul; Tim A. Benke; Eric D. Marsh; Jane B. Lane; David N. Lieberman; Steven A. Skinner; Daniel G. Glaze; Bernhard Suter; Peter T. Heydemann; Arthur A. Beisang; Shannon M. Standridge; Robin C. C. Ryther; et al. (Wiley, 2023)
Abstract Objective We aimed to determine the longitudinal distribution of hand function skills in individuals with classic Rett syndrome (RTT), an X‐linked dominant neurodevelopmental disorder, and correlate with MECP2 variants. Method We conducted a longitudinal study of 946 girls and young women with typical RTT seen between 2006 and 2021 in the US Natural History Study (NHS) featuring a structured clinical evaluation to assess the level of hand function skills. The specific focus of this study was to assess longitudinal variation of hand skills from age 2 through age 18 years in relation to specific MECP2 variant groups. Results Following the initial regression period, hand function continues to decline across the age spectrum in individuals with RTT. Specific differences are noted with steeper declines in hand function among those with milder variants (Group A: R133C, R294X, R306C, and C‐terminal truncations) compared with groups composed of individuals with more severe variants. Conclusions These temporal variations in hand use represent specific considerations that could influence the design of clinical trials that test therapies aiming to ameliorate specific functional limitations in individuals with RTT. Furthermore, the distinct impact of specific MECP2 variants on clinical severity, especially related to hand use, should be considered in such interventional trials.